Freshwater mussel populations in Pacific Coast Watersheds (Oregon, USA): occurrence, condition, habitat, and fish species overlap - Kaegan Scully-Engelmeyer; Emilie Blevins; Elise F. Granek; Ron Constable (Hydrobiologia, 2023)
In the western US, freshwater mussels (Order Unionida) contribute valuable ecosystem functions to riverine systems, yet have declined across their range following widespread degradation of freshwater habitat and parallel declines in salmonids, host fish for larval western pearlshell mussels ( Margaritifera falcata ). The status of M. falcata populations is of particular conservation interest in isolated coastal watersheds given unique freshwater mussel-host fish relationships. To understand M. falcata population ecology in Oregon’s coastal watersheds, we analyzed stream survey data on presence/absence of mussels collected over a recent eleven-year period, explored co-varying habitat characteristics, and summarized mussel distribution and host fish co-occurrence. We also collected M. falcata and compared condition indices among eight locations. Naïve occupancy in surveyed areas was 12.3%, about half of predicted occupancy ( ψ = 0.24, CI 0.19–0.31) based on modeling repeated visits over a ten year assumed closed period. Mussel occupancy was correlated with reach-scale habitat variables, and the probability of mussel observations was positively correlated with presence of coho ( Oncorhynchus kisutch ) salmon. Condition varied significantly among locations. Spatial relationships between existing mussel distribution, host species, and habitat variables answer questions about coastal freshwater mussel populations, as well as serve to identify priorities for further research and population assessment.